Some Dombi aggregation operators based on complex q-rung orthopair fuzzy sets and their application to multi-attribute decision making - Ali, Zeeshan; Mahmood, Tahir (Computational & applied mathematics, 2022)
Dombi aggregation operators (DAOs) are massive flexible and much consistent to manage convoluted and awkward information genuine life troubles. The goal of this manuscript is to initiate the complex q-rung orthopair fuzzy Dombi-weighted averaging (CQROFDWA), complex q-rung orthopair fuzzy Dombi-ordered weighted averaging (CQROFDOWA), complex q-rung orthopair fuzzy Dombi hybrid-weighted averaging (CQROFDHWA), complex q-rung orthopair fuzzy Dombi weighted geometric (CQROFDWG), complex q-rung orthopair fuzzy Dombi-ordered weighted geometric (CQROFDOWG), complex q-rung orthopair fuzzy Dombi hybrid weighted geometric (CQROFDHWG) operators, and demonstrated their important properties. Moreover, by considering these elaborated operators, the multi-attribute decision-making (MADM) technique is developed with the help of certain examples and determined the dominancy and consistency of the presented operators. To determine the supremacy of the elaborated operators, the sensitivity analysis and geometrical expressions of the initiated works are also deliberated.